Physical and mechanical properties of concrete containing fibers from industrial carpet waste - Mohammadhosseini, Hossein (2014)
Fiber reinforcement can effectively improve the mechanical properties of concrete. Utilization of recycled fibers from post-consumer and industrial waste offer some benefits such as waste reduction and resource conservation and also low-cost materials and reduced need for landfilling. Carpets are one of the major components of waste materials around the world, which is 1-2% of all solid wastes by volume. Industrial carpets are mainly made of polymeric materials such as Nylon and Polypropylene fibers. This study was carried out on different tests of the concrete containing fibers from Malaysian industrial carpet waste following the DOE mix design for the investigation of the physical and mechanical properties of concrete. Compressive, splitting tensile and flexural tests were performed with a fiber volume fraction range of 0.5-2%. A decrease in compressive strength and workability was observed as a function of carpet fiber content. However, the addition of carpet fiber leads to enhance the splitting tensile strength, flexural strength and reducing the crack-size and a smoother mode of failure, unlike the brittle failure behavior of plain concrete. Physical and mechanical properties of concrete containing fibers from industrial carpet waste.